2021
DOI: 10.1111/add.15736
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the population‐level impact of opioid agonist treatment on mortality among people accessing treatment between 2001 and 2020 in New South Wales, Australia

Abstract: Background and Aims The individual‐level effectiveness of opioid agonist treatment (OAT) in reducing mortality is well established, but there is less evidence on population‐level benefits. We use modeling informed with linked data from the OAT program in New South Wales (NSW), Australia, to estimate the impact of OAT provision in the community and prisons on mortality and the impact of eliminating excess mortality during OAT initiation/discontinuation. Design Dynamic modeling. Setting and participants A cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Few were in treatment at the time of death. Increasing the proportion in treatment of the population of those who use heroin is of paramount importance, as enrolment in a treatment programme substantially reduces the risk of overdose and death [48]. Among the cases in this study, although medical intervention occurred in a third, most of which may be reasonably assumed to have involved naloxone administration, blood naloxone was detected in only 5%.…”
Section: Discussionmentioning
confidence: 93%
“…Few were in treatment at the time of death. Increasing the proportion in treatment of the population of those who use heroin is of paramount importance, as enrolment in a treatment programme substantially reduces the risk of overdose and death [48]. Among the cases in this study, although medical intervention occurred in a third, most of which may be reasonably assumed to have involved naloxone administration, blood naloxone was detected in only 5%.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings would suggest that changes introduced to the delivery of OAT facilitated increased coverage of OAT in Ireland, an important protective factor for reducing overdose and all-cause mortality (Chaillon et al, 2022;Santo et al, 2021). While the study found a peak in the number of people starting treatment in April 2020, 59 % of whom had prior treatment experience, this increase in starting or re-entering OAT was not sustained in the short or long term.…”
Section: Discussionmentioning
confidence: 61%
“…An obvious way to provide such management is enrolment in a drug treatment programme. Enrolment in a treatment programme substantially reduces the risk of overdose and death, and also improves the health of those enrolled, particularly older people ( Chaillon et al, 2022 ; Fareed et al, 2009 ; Larney et al, 2023 ; Mannelli, 2021 ). Buprenorphine, in particular, has been demonstrated to reduce overdose mortality for older people enrolled in opioid substitution treatment, and for those with cardiovascular and respiratory disease ( Larney et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%